“Da favela para o mundo”: o funk e o reexistir de jovens adolescentes na EJA e na cidade - Adelson Afonso da Silva França Júnior (2019)
The present work sought to investigate the ways in which periphery students enrolled in Youth and Adult Education (EJA), young adolescents, aged 15 to 17 years, build their juvenile identities, having as reference their relations with the funk culture and the city of Belo Horizonte. The methodological option was focused on qualitative research in order to understand the ways of being a young producer of knowledge of funk culture in the periphery and its articulations with the territory and the school of EJA. Thus, the research subjects were four students who routinely engage in dances held in three communities in a bordering region between the cities of Belo Horizonte and Contagem, namely: “Subaco das Cobras”, “Morro da Vaca” and "Morro dos Cabritos". They were interviewed and accompanied at some of these events. To address this issue, we resorted to the categories of periphery, identity, culture and youth conditions. To this end, we turn to authors who address these issues, such as Arroyo (2017), Carrano (2015), Dayrell (2016) and Sposito (2011). The text problematizes the realization of the right to the city, denouncing the (in) visible barriers to which young people are subjected, the decontextualization of public policies, focused on Youth and Adult Education, as well as the decontextualization of the pedagogical practices of the school in relation to the realities experienced by him / her. The work points to the importance of funk culture in the construction of juvenile peripheral identities that present themselves as processes of resistance and re-existences in the face of systematic denial of rights. It also indicates the need and some possibilities to rethink the pedagogical practice with young adolescents in the YAE, in face of this analyzed reality.